K1 Gaps between needs and provision of services in huntington's disease: a cross-sectional population study. (13th September 2016) - Walsem, Marleen R van; Howe, Emilie I; Frich, Jan; Andelic, Nada
Abstract : Background: Despite promising ongoing clinical trials there is no curative treatment for Huntington's disease (HD), and patients need tailored comprehensive healthcare for optimal function and quality of life. No studies have systematically investigated the unmet needs for healthcare and social services or their associations with other factors such as patients' quality of life. Aims: The present study aims to identify the level and type of unmet healthcare service needs using a newly developed scale, the Needs and Provision Complexity Scale (NPCS), and to examine associations with clinical and socio-demographic factors. Methods: 86 patients living in South-East Norway were included in a cross-sectional population based study. Socio-demographic and clinical characteristics were collected. We used the NPCS to evaluate unmet healthcare services needs, the Unified Huntington's Disease Rating Scale's Total Functional Capacity to measure functional ability (stages I-V), and EQ-5D Visual Analogue Scale to assess health-related Quality of Life (HRQoL). Descriptive and multivariate regression analyses were used. Results: 79 patients reported unmet needs for healthcare and social services. High levels of unmet needs were found in all disease stages, but being in stage III increased the odds of having a high level of unmet needs by 3.5 times. Higher levels of unmet needs were associated with lower HRQoL (β value: −0.228; p = 0.018). Conclusions: Many patients do not receive the tailored care they need to maintain and improve function and quality of life. Clinicians should systematically assess needs for healthcare and social services, in addition to performing clinical evaluations, specifically of patients in the middle disease stage. Norway is a well-fare state, and these findings indicate that increased awareness of HD is needed on the policy level. Studies from different countries are needed to verify the results across differently organised health-care systems.